Theory and numerical simulation study on the plastic slip failure mechanism of multi-layered coal seam Floors-A case analysis - Kong, Zheng; Chen, Xuyang; Wang, Xufeng; Zhang, Dongsheng; Chen, Liang; Guo, Shiru (Frontiers in Earth Science, 2025)
Coal seam mining induces disturbances in underground floors, leading to plastic failure, which presents significant safety risks, particularly in areas with underlying pressurized water. Accurately assessing the maximum depth of such floor failure is crucial for ensuring safe mining operations. This study investigates the evolution of apparent resistivity in the floor of the 4,301 working face using the network parallel electrical method. The observed maximum failure depth was found to be 19.3 m. Based on these measurements, the plastic slip theory for a homogeneous rock layer was applied, incorporating mining parameters such as burial depth and mining height. Five mechanical models for plastic slip failure in multi-layer composite floors were developed, with the maximum failure depth calculated to be 18.26 m. The study also explores the impact of factors such as mining height, burial depth, and the internal friction angle of the rock layers on floor failure depth. The results demonstrate that multi-layer composite floors exhibit a 23.1% reduction in failure depth on average compared to homogeneous floors. Numerical simulations confirmed that the maximum failure depth under mining disturbance is 19.2 m, with shear failure identified as the predominant failure mode. The findings from the theoretical analysis, numerical simulations, and field measurements align closely, validating the applicability of the plastic slip theory for multi-layer composite floors. This research provides critical theoretical support for safe mining operations in coal seams above confined aquifers and effective water control strategies.